Mechanical behaviour of corrugated laminates - Pinheiro, D. J. G. (2019)
The present research work intends to perform a wide set of structural analyses upon corrugated composite laminated panels and based on these analyses, to assess their mechanical response in correspondence to the constructive solutions, which may range from the composite materials selection to the geometrical features and other modelling parameters. To improve the mechanical performance of those panels one may consider enhancing their geometrical characteristics, their corrugation shape configuration and the materials used to build them. In this latter case, when considering materials selection, laminated composites may also constitute an important alternative. In any case it is considered necessary to assess the impact that each of these parameters may have in the static and in the free vibration behaviour of the structures, in a comprehensive and detailed way. To achieve the main objective of this research work, a comprehensive and diversified set of case studies is considered in order to characterize the influence that each of the modelling, material and geometrical parameters and characteristics may have in the mechanical response of a corrugated panel. This study allowed concluding that for the wide set of design parameters considered, the fibre orientation and corrugation parameters are the ones responsible for the majority of the significantly improved performances.